2007
DOI: 10.1080/09602010701381933
|View full text |Cite
|
Sign up to set email alerts
|

Using a paging system in the rehabilitation of encephalitic patients

Abstract: Memory and executive problems following encephalitis are common yet there are few published papers on the successful rehabilitation of such patients. We recently demonstrated (Wilson, Emslie, Quirk, & Evans, 2001; Wilson, Emslie, Quirk, Evans, & Watson, 2005) that a paging system could reduce the everyday memory and planning problems for people with non-progressive brain injury. Among the 143 patients who participated in the 2001 study were four people who had survived encephalitis. Their results are reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 10 publications
3
21
0
Order By: Relevance
“…37 The use of a paging system for prospective memory tasks resulted in improved completion of target behaviors when using a pager, with reduced carryover without the pager, for 3 subjects. 40 These results, similar to those obtained with a comparable TBI group, supported the use of a pager for individuals with moderate to severe memory deficits. Use of a memory notebook was associated with improved memory management in 2 singlesubject studies, 38,39 the latter subject returning to her job 8 months postillness.…”
Section: Encephalitissupporting
confidence: 78%
See 1 more Smart Citation
“…37 The use of a paging system for prospective memory tasks resulted in improved completion of target behaviors when using a pager, with reduced carryover without the pager, for 3 subjects. 40 These results, similar to those obtained with a comparable TBI group, supported the use of a pager for individuals with moderate to severe memory deficits. Use of a memory notebook was associated with improved memory management in 2 singlesubject studies, 38,39 the latter subject returning to her job 8 months postillness.…”
Section: Encephalitissupporting
confidence: 78%
“…[37][38][39][40][41][42][43][44] Four case reports or single-subject studies 37-40 investigated either the use of external aids or strategies to improve memory performance. The use of a wearable camera that takes pictures automatically every 30 seconds was found to be more effective than a written diary in improving autobiographical recall for a woman with severe memory impairment, with carryover effects evident after 3 months.…”
Section: Encephalitismentioning
confidence: 99%
“…This study has shown that a paging system is effective in compensating for the everyday memory and planning problems of a group of patients with brain injury of mixed cerebrovascular aetiology, and that these clinical benefits are of a similar magnitude to those reported for patients with memory problems following TBI21 and encephalitis 27. Participants typically showed a 30% increase in goal attainment with use of the pager.…”
Section: Discussionmentioning
confidence: 57%
“…One of the reasons for this discrepancy might be that these patients might not primarily have memory impairments, but executive dysfunctions that are not captured by the RBMT. In a recent study by Emslie and colleagues (31), findings revealed that executive difficulties might affect treatment for using a pager. This indicated that it is important to assess executive functions in combination with an evaluation of compensatory aids.…”
Section: Discussionmentioning
confidence: 98%